Experimental Study on the Influence of Jet Dynamic Pressure Based on a New Confining Pressure Control System - Zhou Shijie; Lü Weiping; Liu Jiawei; Zhang Zheng; Zhu Ye; Luo Bin (Shiyou jixie)
To address challenges such as low operating efficiency and poor descaling effect in jet stimulation operation of deep/ultra-deep wells， the influence of downhole environmental pressure （confining pressure） on jet dynamic pressure has been studied at home and abroad. The confining pressure loaded in the previous study is mainly below 20 MPa， and the throttling method is used to adjust the pressure， which is inconvenient to control and the accuracy is not high. In this paper， a self-developed high confining pressure control system was used for simulation of higher confining pressure， achieving 0~100 MPa stepless pressure regulation， and monitoring the jet dynamic pressure and confining pressure in real time. Moreover， the experimental error possibly existed in the system was evaluated， and a preliminary test of confining pressure ≤55 MPa was carried out， verifying the feasibility of the new confining pressure loading system. The study results show that when the confining pressure is less than or equal to 10 MPa， the jet dynamic pressure decays significantly. As the confining pressure increases， the attenuation amplitude of jet dynamic pressure gradually decreases. The study results guide the jet operation of ultra-deep wells， and lay a foundation for further consolidating the jet attenuation characteristics under confining pressure and improving the theory of jet attenuation under high confining pressure.